Analisis Kemenangan Ahmad Heryawan Dalam Pemilu Kepala Daerah Jawa Barat Tahun 2013 - Joni Firmansyah; Hermini Susiatiningsih; Supratiwi . (Journal of Politic and Government Studies, 2014)
Partai Keadilan Sejahtera is one of political party which take part of political dynamics in Indonesia. One of political dynamics that occur is the winning of PKS’s cadre, he is Ahmad Heryawan who selected in Jawa Barat head election in 2013. The winning became interesting when Ahmad Heryawan can win the political struggle in the condition that PKS get corruption case which attack the internal party. Researcher try to elaborate many factor which influence Ahmad Heryawan winning within corruption case of beef imports. The purpose of research is to know many factor that influence Ahmad Heryawan winning in Jawa Barat head election in 2013. This research involve nine of informant who take part the process of Jawa Barat head election. The typical of this research is qualitative type with descriptive analysis model. The data retrieved by way of interview process and document from PKS and KPUD Jawa Barat. Based on research result, there are five factors that affect Ahmad Heryawan winning in Jawa Barat head election. The five factors are imaging factor of Ahmad Heryawan, Deddy Mizwar’s factor as mass getter, achievement factor of Ahmad Heryawan and incumbent position, the power of political party engine, and the winning team power. Moreover, there are some supporting factors such us chances of winning Ahmad Heryawan that greater than the nearest rival in the vote, Rieke Diah Pitaloka. This occurs because PDIP late in preparing cadres. From the overall factors, imaging factor is the most dominant.